2020
DOI: 10.1007/978-981-15-4409-5_28
|View full text |Cite
|
Sign up to set email alerts
|

Automation of the Requisition Process in Material Supply Chain of Construction Firms

Abstract: Construction materials play a crucial role in the project delivery process. However, the process of requisition for the materials on construction site if not handled appropriately can adversely affect the performance of quality, cost, and time. Therefore, the study was aimed at developing an automated materials requisition system which will make the supply chain on construction sites seamless and more effective. A use case diagram and an activity block diagram helped to understand the users and functionalities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Because each phase of OSC project execution-production, transportation, and installation-is critical for project success [27], the literature has suggested new managerial methods. Researchers have focused on optimization theory with respect to the production phase occurring at off-site factories that emulate the manufacturing environment.…”
Section: Literature Review 21 Osc Project Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Because each phase of OSC project execution-production, transportation, and installation-is critical for project success [27], the literature has suggested new managerial methods. Researchers have focused on optimization theory with respect to the production phase occurring at off-site factories that emulate the manufacturing environment.…”
Section: Literature Review 21 Osc Project Managementmentioning
confidence: 99%
“…Furthermore, Abdula and Usman [30] identified factors impeding the lean supply chain flow of all resources through the six-sigma method, and Ismail [31] applied ANN and a genetic algorithm to monitor and manage workflows. Several studies identified that integrated management is of paramount importance in OSC projects; each phase is closely linked like a chain [27], focusing on integrated management to fill and bridge the gaps between the project phases. Lee and Lee [18] proposed a digital twin framework for managing schedules during entire processes.…”
Section: Literature Review 21 Osc Project Managementmentioning
confidence: 99%